Time-course of the physiological-stress response in bronze bream Pachymetopon grande following a simulated catch-and-release angling event. Issue 3 (1st October 2020) - Pringle, BA; Childs, A-R; Butler, EC; Winkler, AC; Duncan, MI; Teta, C; Potts, WM
Abstract : Catch-and-release (C&R) angling has increased in popularity through its mandatory and voluntary use in fisheries conservation and management. However, research has shown that fish can experience considerable stress during a C&R event. The physiological response of fishes is typically assessed by measuring the concentrations of blood-plasma cortisol, blood glucose and blood lactate. Members of the family Sparidae are extensively targeted in many warm-temperate coastal fisheries, and the bronze bream Pachymetopon grande is one of the most commonly captured sparids in the South African marine shore-based fishery. The aim of this study was to map the time-course of the physiological-stress response (PSR) after a simulated C&R event to determine the optimal blood-sampling time for assessing the physiological impact of C&R angling in the field. A general additive mixed model identified a significant effect of time on plasma cortisol ( p = 0.005), blood glucose ( p < 0.001) and blood lactate ( p = 0.037), with plasma cortisol peaking at approximately 65 minutes and blood glucose at 86 minutes post-stress. In contrast, blood lactate continued to rise with no clear peak during the 125-minute sampling period. These results suggest that blood sampling should take place between 50 and 75 minutes after a C&R event. Despite a clear response, the PSR of P. grande will likely be greater in a true C&R event as this study made use of a simulated fight and used best handling practices. In addition, the prolonged physiological impacts of C&R may have negative consequences for the survival of this species in the high-energy, predator-rich coastal marine environment.